Designing and Implementing an Internship Unit in the Field of Medical Sciences with an Approach of Occupational Safety and Health in Health and Medical Settings in Torbat Heydariyeh University of Medical Sciences - Maryam FEIZ AREFI; Nayereh KASIRI; Hashem HESHMATI; Mohsen POURSADEGHIYAN (Shahid Sadoughi University of Medical Sciences, 2022)
Introduction: Occupational injuries are one of the most important challenges in health care systems, which can lead to the transmission of infectious diseases. Medical students are at risk due to internships in a clinical setting. Therefore, it is necessary to perform educational measures in this field for them at the beginning of entering the clinical setting. Therefore, the present study aims to implement and design an internship unit in the field of medical sciences with an approach of occupational safety and health in the clinical setting. Methods: In this educational course, after coordination and obtaining approvals, the target group of the study was determined and occupational health and safety educational course was designed and implemented on students who had internships in health centers. The satisfaction with the educational course was assessed. Qualitative assessment and students' work reports in the field of occupational safety and health were also evaluated. Results: At first, students did not have sufficient and coherent information on safety and health issues. The results of this study show that from the perspective of the students, education was good and higher (71.6%) in terms of the applicability of the content. Moreover, 70.1% of the students reported that the adequacy of the education with job responsibilities was good and excellent. More than 80% reported that the workshop was attractive and recommended to continue, 37.3% stated that the educational resources provided with the workshop content were good, and the opinion of 29.8% was very good and excellent. The overall evaluation of the workshop from the students' point of view and quality assessment of the workshop showed that more than 77% of them evaluated the workshop as good and excellent. Conclusion: The educational courses, modification of accident registration forms in students in the clinical setting, and also the existence of clinical accident self-reporting programs, especially for students seem necessary. It is suggested that the concepts of occupational safety and health be added to the content of medical students' courses in the clinical setting as an educational concept. The results of this study can be implemented in the curriculum review to improve the safety of clinical setting.